ANALYSIS OF ELECTRONIC MATERIAL USE OF BASIC MATERIALS, IN EMS STEEL EDM PROCESS 45 REVIEWED FROM THE ASPECTS OF ELECTRODES OF MASS REDUCTION AND SURFACE DAMAGE - Tiwan Tiwan (Jurnal Penelitian Saintek, 2007)
The aim pf  this research is  to analyze characteristic  of Cu-based material that has been used as electrode in EDM process. The research variables are wearness off electrode, weightloss and roughness of specimens of EMS 45 steel.Experimental methode was used in this research, which consists of preparation process and EDM test, EDM process, characterization and testingprocess. Analysis was done based on characterization and testing  process.   Testing process   comprises  electrode  wearness, weightloss and roughness of the specimen.The result show that wearness of brass electrode is higher than bronze electrode. However, bronze electrode gives  rapid  weight  loss. At current of 45 A and pulse on time 3 s, weight loss of EMS 45 steel was1,8 timefaster using bronze electrode, but wearness of brass electrode was  18,67 times faster.  Surface  roughness of EMS  45 steel was smoother using bronze electrode. Weight loss of EMS 45 steel and electrode wearness affected by current andpulse on time. Nevertheles, surface roughness of EMS 45 influenced by current, but not bypulse on time.